Game-Based Learning to Improve Spatial Ability from the Perspective of Maier's Theory in Geography Learning - Astagini Putri Kariana; Siti Sanisah; Arif; Mas'ad; Nurin Rochayati (Journal of Education Action Reseach, 2026)
The spatial ability of students in Indonesia, especially at the Junior High School level, is still underdeveloped, due to several factors, including the dominance of conventional learning that minimally involves students, is less contextual, and less interactive. This study aims to improve students' spatial ability at MTsN by implementing a Game-Based Learning approach, supported by the traditional game Estafet Sarung, in the Geography sub-subject. The study is included in the Classroom Action Research model of Kemmis and McTaggart, which is carried out in three cycles, each cycle consisting of four stages: plan, act and observe, reflect, and revised plan. The instrument used to measure the success of the action is a multiple-choice test and an essay. The research subjects were 30 students of class VII-B. The research findings show an increase in spatial ability from the initial condition, with an average of 58 increasing to 66 (cycle 1), 76 (cycle 2), 87 (cycle 3), and 89 (posttest). The application of Game-Based Learning is effective in improving students' spatial ability. The implication is that integrating games into geography learning can create interactive and meaningful learning experiences, as well as strengthen student participation, spatial analysis, and interest in learning. Teachers can use this approach as a basis for designing digital-based geography learning, spatial simulations, and interactive geospatial applications. It is recommended that the use of game-based learning, particularly technology-based learning, continue to be developed to strengthen spatial abilities at various levels of education.